Posttraumatic stress in breast cancer survivors diagnosed at a young age. Issue 8 (9th July 2020) - Vazquez, Danny; Rosenberg, Shoshana; Gelber, Shari; Ruddy, Kathryn J.; Morgan, Evan; Recklitis, Christopher; Come, Steven; Schapira, Lidia; Partridge, Ann H.
Abstract: Objective: Young breast cancer patients experience greater psychosocial distress compared with older patients, which raises concern for their risk of posttraumatic stress disorder (PTSD). We sought to characterize the prevalence of clinically significant symptoms of PTSD and associated factors among breast cancer survivors diagnosed at a young age. Methods: The Young Women's Breast Cancer Study, an ongoing prospective cohort study, enrolled 1302 women diagnosed with breast cancer at age ≤ 40 between 2006 and 2016. Participants complete serial surveys, and we obtained additional information from medical record review. Socio‐demographics, anxiety and depression, social support, and psychiatric co‐morbidities and medications were assessed at study baseline (median, 5 months post‐diagnosis). We defined a participant as having clinically significant posttraumatic stress symptoms (PTSS) by scoring ≥50 on the PTSD Checklist‐Specific Version, administered on the 30‐month survey. Results: Among 700 women with stage 1‐3 disease, the prevalence of PTSS was 6.3% (95%CI = 4.5‐8.1). In multivariable analyses, PTSS was significantly associated with anxiety (OR 12.43, 95%CI = 5.81‐26.59, P < .0001) and stage 2 vs 1 disease (OR 2.26, 95%CI = 1.04‐4.93, P = .04). PTSS was inversely associated with having a college degree (OR 0.29, 95%CI = 0.13‐0.62, P = .002) and greater social support (OR 0.44, 95%CI = 0.21‐0.94, P = .03). Conclusions: We found similar rates of cancer‐related PTSS in breast cancer survivors diagnosed at a young age compared with the general breast cancer population despite their well‐documented increased risk of overall distress. Nevertheless, factors associated with posttraumatic stress should be considered at diagnosis and in survivorship to identify young patients who may benefit from psychosocial resources.